1980
DOI: 10.1111/j.1476-5381.1980.tb10701.x
|View full text |Cite
|
Sign up to set email alerts
|

β‐ADRENOCEPTOR ANTAGONISTS: STUDIES ON BEHAVIOUR (DELAYED DIFFERENTIATION) IN THE MONKEY (Macaca mulatta)

Abstract: IActivity of six ,B-adrenoceptor antagonists was studied on behavioural activity (delayed differentiation) in the monkey (Macaca mulatta). The drugs, three relatively lipophilic antagonists (propranolol, oxprenolol and metoprolol), and three relatively hydrophilic antagonists (acebutolol, atenolol and sotalol), were given by intraperitoneal injection (5 to 30 mg/kg). 2 With atenolol (25 to 30 mg/kg), total response time was increased, but there was no effect on the number of correct responses. With acebutolol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1981
1981
2002
2002

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Nicholson & Wright (1980) suggested that membrane stabilisation may be a basis for the central effects of propranolol. It was worth noting that the most frequently observed side effects of propranolol were drowsiness, ataxia and hypotension, not bradycardia or congestive heart failure, in psychiatric patients who took large doses of propranolol (up to 600 mg QDS) for the control of schizophrenic symptoms (Sheppard, 1979).…”
Section: Discussionmentioning
confidence: 98%
“…Nicholson & Wright (1980) suggested that membrane stabilisation may be a basis for the central effects of propranolol. It was worth noting that the most frequently observed side effects of propranolol were drowsiness, ataxia and hypotension, not bradycardia or congestive heart failure, in psychiatric patients who took large doses of propranolol (up to 600 mg QDS) for the control of schizophrenic symptoms (Sheppard, 1979).…”
Section: Discussionmentioning
confidence: 98%
“…Drugs which impair performance, such as oxazepam and diazepam, modify body sway, whereas similar drugs without obvious behavioural effects, such as clobazam, dipotassium chlorazepate and desmethyldiazepam tend to leave body sway unaffected (Baron et al, 1977;Sittig et al, 1982;Patat & Foulhoux, 1985). However, the effect of atenolol could have been mediated through the peripheral control of posture, since impaired psychomotor performance is not an obvious effect of this drug (Nicholson & Wright, 1980;Currie et al, 1988).…”
Section: Electroencephalogramsmentioning
confidence: 99%